Improving the Acceptability of Human Papillomavirus Vaccines Among Men Who Have Sex With Men According to the Associated Factors: A Systematic Review and Meta-analysis - Zhao, Yang; Xin, Xiaoli; Deng, Huiwen; Xu, Junjie; Weng, Wenjia; Zhang, Ming; Li, Juan; Gao, Yanqing; Huang, Xiaojie; Liu, Cuie (Frontiers in Pharmacology, 2021)
Objectives: To investigate the acceptability of human papillomavirus (HPV) vaccination among men who have sex with men (MSM) and its associated factors. Methods: We searched studies written in English in PubMed, EMBASE, and Web of Science with no geographical or time restrictions. We evaluated the quality of the included literature. We calculated the weighted mean acceptability and then performed meta-analysis of selected studies, including factors associated with the acceptability among MSM, using Review Manager (v5.3). Results: The weighted mean acceptability among the 15 studies (n = 8658) was 50% (95% CI: 0.27 to 0.72). The meta-analysis of seven articles (n = 4200) indicated that having a college or higher degree (OR = 1.62, 95% CI: 1.35 to 1.95), disclosure of sexual orientation to healthcare professionals (HCPs; OR = 2.38, 95% CI: 1.47 to 3.86), vaccination with at least one dose for hepatitis A or B (OR = 2.10, 95% CI: 1.42 to 3.10), awareness of HPV (OR = 1.85, 95% CI: 1.21 to 2.83), knowledge of HPV (SMD = 0.28, 95% CI: 0.16 to 0.39), perceived susceptibility to HPV infection (SMD = 0.31, 95% CI: 0.11 to 0.50), and perceived severity of HPV-related disease (SMD = 0.40, 95% CI: 0.28 to 0.51) can promote acceptance of HPV vaccines. Meanwhile, people who have had unprotected anal sex or have more sex partners tend to have low acceptance of HPV vaccines. Conclusions: HPV education should be actively promoted according to the factors that influence the acceptability of HPV vaccines among the MSM population. HPV education should be especially aimed at people with low academic qualifications and people with risky sexual behaviours, and should emphasise the aspects of susceptibility to and severity of HPV-related disease. More intervention trials should be conducted to increase the credibility of the results.